Exercise capacity of vegan, lacto-ovo-vegetarian and omnivorous recreational runners - Josefine Nebl (Journal of the International Society of Sports Nutrition, 2019)
Abstract Background In search of the right nutrition for the athlete, numerous nutritional strategies and diets were discussed over time. However, the influence of plant-based diets, especially veganism, on exercise capacity has not been clarified. Methods We conducted a cross-sectional study to compare the exercise capacity of vegan (VEG, n = 24), lacto-ovo-vegetarian (LOV, n = 26) and omnivorous (OMN, n = 26) recreational runners. To determine maximal exercise capacity, participants performed an incremental exercise test on a bicycle ergometer until voluntary exhaustion. During the test capillary blood samples were taken at several time points for the measurement of arterial lactate [lac] and glucose [glc] concentrations. To determine nutrient intake, a 24 h dietary recall was conducted. Results The groups showed comparable training habits in terms of training frequency (mean 3.08 ± 0.90 time/wk., p = 0.735), time (mean 2.93 ± 1.34 h/wk., p = 0.079) and running distance (mean 29.5 ± 14.3 km/wk., p = 0.054). Moreover, similar maximum power output (PmaxBW) was observed in all three groups (OMN: 4.15 ± 0.48 W/kg, LOV: 4.20 ± 0.47 W/kg, VEG: 4.16 ± 0.55 W/kg; p = 0.917) and no differences regarding [lac] throughout the exercise test and maximum lactate could be observed between the groups (OMN: 11.3 ± 2.19 mmol/l, LOV: 11.0 ± 2.59 mmol/l, VEG: 11.9 ± 1.98 mmol/l; p = 0.648). Conclusion The data indicate that each examined diet has neither advantages nor disadvantages with regard to exercise capacity. These results suggest that a vegan diet can be a suitable alternative for ambitious recreational runners. Trial registration German Clinical Trials Register (DRKS00012377). Registered on 28 April 2017